RISK FACTORS FOR KINESIOPHOBIA AMONG ORTHOPAEDIC PATIENTS - A LITERATURE REVIEW - Magdalena Gostół,; Anna Wawrzeczko,; Maciej Krzysztof Jakubiec,; Angelika Jankowska,; Natalia Górska,; Katarzyna Wójtowicz,; Gabriela Deska,; Emilia Gąsiorowska,; Aleksandra Lewczuk, (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Kinesiophobia, defined as an excessive and unjustified fear of movement resulting from fear of pain or re-injury (Reneman et al., 2003), is a significant factor limiting the effectiveness of rehabilitation after orthopaedic surgery. A growing number of studies indicate that its development is multifactorial and goes beyond purely biomechanical postoperative conditions.Aim of the study: The aim of this literature review was to identify and analyse the risk factors for kinesiophobia among orthopaedic patients.Material and methods: A review of observational studies, systematic reviews and meta-analyses published between 2018 and 2025 in PubMed and Google Scholar databases was conducted in the following patient populations: total knee arthroplasty, ACL and MPFL reconstruction, limb fracture fixation, rotator cuff repair, lumbar spinal fusion and articular cartilage damage.Results: The most commonly identified risk factors were: high postoperative pain intensity, the presence of anxiety and depressive symptoms, low self-efficacy and avoidance strategies for coping with stress. Sociodemographic factors such as older age, poor social support, and lower education level were also significant. High levels of kinesiophobia correlate with more limited range of motion and delayed return to function. Analyses indicate that in some patients, kinesiophobia persists over time, especially in the presence of multimorbidity. Pre-injury level of sports activity, prolonged injury-to-surgery time, gender and abnormal BMI may be additional predictors. A correlation was also found between the type of anesthesia used during surgery and the level of kinesiophobia in the early postoperative period.Conclusions: Kinesiophobia affects a large group of orthopedic patients suffering from various conditions. It is a phenomenon with biopsychosocial causes. Early identification of patients with risk factors may enable implementation of targeted interventions and improve treatment outcomes.